(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Definitions of inside and relevant information. Four arguments that prove that Insider Trading is not ethical. Origins of the contrary opinion: a) Misinterpretation of the concept about the Invisible Hand by Adam Smith as something similar to the Law of Universal Gravitation described by Sir Isaac Newton; b) Two writings by Henry G. Manne. Historical and legal data, two recent Codes of Ethics and four cases.